Prognostic significance of a combination of novel biomarkers in the long-term stratification of adverse outcomes in patients with ST-segment elevation myocardial infarction - D. F. Gareeva; A. F. Khamitova; I. A. Lakman; R. P. Ronzhin; R. Kh. Zulkarneev; M. R. Plotnikova; E. L. Tulbaev; L. J. Motloch; N. Sh. Zagidullin (Российский кардиологический журнал, 2020)
A multi-marker approach for assessing the prognosis of patients with ST-segment elevation myocardial infarction (STEMI) is a promising strategy.Aim. To assess the potential prognostic power of soluble growth stimulation gene-2 (sST2), pentraxin 3 (PTX3), and N-terminal pro-brain natriuretic peptide (NT-proBNP) in stratification of the risk of major cardiovascular events (CVE) during 2-year follow-up after STEMI.Material and methods. In 154 patients with STEMI, serum concentrations of NT-proBNP, sST2, and PTx-3 were determined upon admission to hospital. During the two-year follow-up period (734,2±61,2 days), correlation of biomarker concentrations with the risk of a composite endpoint (myocardial infarction + stroke + hospitalization due to cardiovascular disease + cardiovascular death) was analyzed.Results. In the 2-year follow-up, CVE were observed in 81 (55,1%) patients (CV death (n=33; 22,1%), recurrent MI (n=28; 18,.8%), stroke (n=8; 5,4%), hospitalization due to cardiovascular disease other than MI, stroke or cardiovascular death (n=12; 8,2%)). NT-proBNP (HR, 1,19; 95% CI, 1,018-1,32, p<0,001) and sST2 (HR, 1,000013; 95% CI, 1,00-1,001, p=0,007) correlated with CVE in contrast to PTX-3 (HR, 1,178; 95% CI, 0,798-1,73, p=0,434). The most accurate prediction of CVE was shown in the model with three biomarkers (AIC=831, BIC=843, LR=12,45, p=0,033). Conclusion. After STEMI, NT-proBNP and sST2, but not PTX-3, predicted CVE, while 3-marker analysis showed higher accuracy compared to single- and doublemarker.